SERVICESCAPE FACTORS ON HIGHER EDUCATION LIBRARY - Mamahit, Suzanna Katharina (Universitas Brawijaya, Indonesia, 2017)
The purpose of a college library is to meet the needs of lecturers who conduct teaching and learning processes and who concern Three College Dharma (teaching, research and community service). It is necessary to consider factors underlying users'reasons to visit libraries. Using exploratory quantitative methods, this paper aims to investigate servicescape library factors that affect users' interests. Data were collected through questionnaires containing twenty five statements related to college library servicescape. The population as well as the sample of this study involved 346 respondents such as lecturers, students and staff. This study found college library serviscape factors were obtained through five stages such as data preparation stage; extraction factor stage; axis rotation factor stage; model operation stage and result use stage. Likert scale model was employed to score each statement in the questionnaires. Five factors were grouped such as cleanliness and comfortable facilities, aesthetic facilities, accessibility to layout, facility appearance and functionality of facilities. The factor with the lowest mean of 3.58 was Fungctionality of the Facilities. This factor included the room light indicator; appropriate lighting (sunlight); convenient library opening hours for users; adequate lockers/caretaker and adequate carrel reading/study desk.